Single low dose primaquine to block the transmission of Plasmodium falciparum—proposed stand-alone and ACT-adapted regimens - Walter R. J. Taylor; Peter Olupot-Olupot; Marie A. Onyamboko; Natenapa Chimjinda; Chiraporn Taya; Julie Nguyen Ngoc Pouplin; Thomas N. Williams; Kathryn Maitland; Caterina A. Fanello; Nicholas P. J. Day; Joel Tarning; Nicholas J. White; et al. (BMC Medicine)
Abstract Background Despite the 2012 WHO recommendation to add single low dose primaquine (SLDPQ, 0.25 mg/kg body weight) to artemisinin-based combination treatments (ACTs) for blocking the transmission of artemisinin-resistant Plasmodium falciparum, there are currently no weight-based regimens founded on robust evidence. Methods Applying published safety, transmission blocking and pharmacokinetic data, and exploring pharmacokinetic-pharmacodynamic relationships of age-based dosing of SLDPQ in African children with acute, uncomplicated Plasmodium falciparum, we derived weight-based, stand-alone, ACT-, triple ACT-, and vivax-matched regimens by following allometric dosing principles and simulating PQ exposure (area under the concentration time curve). The ACTs were dihydroartemisinin piperaquine (DHAPP), artesunate pyronaridine (ASPYR), artesunate amodiaquine (ASAQ), artesunate mefloquine (ASMQ), artemether lumefantrine (AL), and ALAQ. Tablet strengths were predefined: 2.5, 3.75, 5, 7.5, and 15 mg, and no tablet fractions were allowed. The maximum mg/kg dose was set at 0.5, and, primarily for ease of ACT co-blistering, 1 tablet = 1 dose. We assessed different mg/kg doses and selected the dosing associated with a predicted median exposure closest to 1200 ng*h/mL, the exposure predicted for a 60 kg individual given 15 mg of PQ. Results The designed 8 regimens had 4–8 dosing bands. The stand-alone, DHAPP, and ASPYR regimens contain the full line of PQ tablets and all other regimens, except AL (2.5, 7.5, 15 mg) and ALAQ (2.5, 5, 7.5, 15 mg), use 3.75 mg. The 2.5 mg tablet resulted in a maximum dose of 0.56 mg/kg for ASAQ, as this regimen starts at 4.5 kg body weight, whilst all other regimens start at 5 kg and resulted in 0.5 mg/kg. Substituting 3.75 mg with 5 mg results in maximum doses of 0.56 mg/kg (ASAQ, ASMQ) and 0.63 mg/kg (other regimens), risking greater toxicity. Across all dosing bands, 0.17 − 0.56 mg/kg doses predict exposures of ~ 500 − 2000 ng*mL/h. Regimens with more dosing bands had less variations in exposure. Conclusions These regimens offer flexibility for malaria control programmes and guidance for drug manufacturers wishing to co-blister SLDPQ with ACTs. The WHO should reinstate the 3.75 mg tablet for prequalification and determine which regimens should be incorporated into their treatment guidelines to advance malaria elimination. Trial registration The trial is registered at ISRCTN, number 11594437.